2014
DOI: 10.1007/978-3-319-06734-6_12
|View full text |Cite
|
Sign up to set email alerts
|

New Attacks on the RSA Cryptosystem

Abstract: Abstract. This paper presents three new attacks on the RSA cryptosystem. The first two attacks work when k RSA public keys (Ni, ei) are such that there exist k relations of the shape eix − yiφ(Ni) = zi or of the shape eixi − yφ(Ni) = zi where Ni = piqi, φ(Ni) = (pi − 1)(qi − 1) and the parameters x, xi, y, yi, zi are suitably small in terms of the prime factors of the moduli. We show that our attacks enable us to simultaneously factor the k RSA moduli Ni. The third attack works when the prime factors p and q o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 16 publications
0
19
2
Order By: Relevance
“…From our result, one can observe that we get d ≈ N 0.3706 , which is larger than Blömer-May's bound x < 1 3 N 0.25 , as reported in Reference [12]. Our d ≈ N 0.3706 is also larger than Nitaj et al's bound d ≈ N 0.344 , as reported in Reference [13] .…”
Section: Examplecontrasting
confidence: 44%
See 1 more Smart Citation
“…From our result, one can observe that we get d ≈ N 0.3706 , which is larger than Blömer-May's bound x < 1 3 N 0.25 , as reported in Reference [12]. Our d ≈ N 0.3706 is also larger than Nitaj et al's bound d ≈ N 0.344 , as reported in Reference [13] .…”
Section: Examplecontrasting
confidence: 44%
“…, N t in polynomial time. We have found decryption exponents bounds that are greater than those of References [12,13].…”
Section: Introductionmentioning
confidence: 63%
“…The ways in which RSA might be attacked are well studied and 20 years ago the attacks were well catalogued [8]. The intervening years has seen new forms of attack reported [9] but the problem is always the efficiency with which we can implement these factoring algorithms on conventional computers.…”
Section: Factoring Algorithmsmentioning
confidence: 99%
“…Extending the result from [16], this paper presents an attack on the modulus N = p 2 q when the primes share a known amount of the LSBs while d 1 and d 2 share an amount of their MSBs. We formulate a lemma by ulitizing the information on the sharing LSBs between the primes.…”
Section: Introductionmentioning
confidence: 97%
“…Sun et al [14] and Zhao et al [15] also showed that using primes that share either most or least significant bits are insecure and the modulus can be factored in polynomial time. Following through in 2014, Nitaj et al [16] came out with an idea to attack the modulus N = pq where the primes share their LSBs and there exists two public parameters e 1 and e 2 such that the corresponding decryption parameters d 1 and d 2 share their MSBs. They showed that if the RSA crytosystem satisfies those conditions, then it is possible to factor N provided…”
Section: Introductionmentioning
confidence: 99%